Huntingtin CAG-expansion mutation results in a dominant negative effect - Laundos, Tiago L.; Li, Shu; Cheang, Eric; De Santis, Riccardo; Piccolo, Francesco M.; Brivanlou, Ali H. (Frontiers in Cell and Developmental Biology, 2023)
Introduction: Huntington’s disease (HD) remains an incurable and fatal neurodegenerative disease long after CAG-expansion mutation in the huntingtin gene (HTT) was identified as the cause. The underlying pathological mechanism, whether HTT loss of function or gain of toxicity results from mutation, remains a matter of debate. Methods: In this study, we genetically modulated wild-type or mutant HTT expression levels in isogenic human embryonic stem cells to systematically investigate their contribution to HD-specific phenotypes. Results: Using highly reproducible and quantifiable in vitro micropattern-based assays, we observed comparable phenotypes with HD mutation and HTT depletion. However, halving endogenous wild-type HTT levels did not strongly recapitulate the HD phenotypes, arguing against a classical loss of function mechanism. Remarkably, expression of CAG-expanded HTT in non-HD cells induced HD like phenotypes akin to HTT depletion. Discussion: By corollary, these results indicate a dominant negative effect of mutated HTT on its wild-type counterpart. Complementation with additional copies of wild-type HTT ameliorated the HD-associated phenotypes, strongly supporting a classical dominant negative mechanism. Understanding the molecular basis of this dominant negative effect will guide the development of efficient clinical strategies to counteract the deleterious impact of mutant HTT on the wild-type HTT function.